Custom-made acetabular revision arthroplasty for pelvic discontinuity: Can we handle the challenge?: a prospective cohort study. (1st February 2023) - Faraj, Sayf; de Windt, Tommy S.; van Hooff, Miranda L.; van Hellemondt, Gijs G.; Spruit, Maarten
Abstract : Aims: The aim of this study was to assess the clinical and radiological results of patients who were revised using a custom-made triflange acetabular component (CTAC) for component loosening and pelvic discontinuity (PD) after previous total hip arthroplasty (THA). Methods: Data were extracted from a single centre prospective database of patients with PD who were treated with a CTAC. Patients were included if they had a follow-up of two years. The Hip Disability and Osteoarthritis Outcome Score (HOOS), modified Oxford Hip Score (mOHS), EurQol EuroQoL five-dimension three-level (EQ-5D-3L) utility, and Numeric Rating Scale (NRS), including visual analogue score (VAS) for pain, were gathered at baseline, and at one- and two-year follow-up. Reasons for revision, and radiological and clinical complications were registered. Trends over time are described and tested for significance and clinical relevance. Results: A total of 18 females with 22 CTACs who had a mean age of 73.5 years (SD 7.7) were included. A significant improvement was found in HOOS (p < 0.0001), mOHS (p < 0.0001), EQ-5D-3L utility (p = 0.003), EQ-5D-3L NRS (p = 0.013), VAS pain rest (p = 0.008), and VAS pain activity (p < 0.0001) between baseline and final follow-up. Minimal clinically important improvement in mOHS and the HOOS Physical Function Short Form (HOOS-PS) was observed in 16 patients (73%) and 14 patients (64%), respectively. Definite healing of the PD was observed in 19 hips (86%). Complications included six cases with broken screws (27%), four cases (18%) with bony fractures, and one case (4.5%) with sciatic nerve paresthesia. One patient with concurrent bilateral PD had revision surgery due to recurrent dislocations. No revision surgery was performed for screw failure or implant breakage. Conclusion: CTAC in patients with THA acetabular loosening and PD can result in stable constructs and significant improvement in functioning and health-related quality of life at two years' follow-up. Further follow-up is necessary to determine the mid- to long-term outcome. Cite this article: Bone Jt Open  2023;4(2):53–61.